A Case Study of Connection Between Ground Magnetic Field Perturbations and Tail Current Sheet Bursty Flows at X = −60 RE. Issue 3 (6th March 2018) - Wang, Chih‐Ping; Xing, Xiaoyan; Liu, Yi‐Hsin; Runov, Andrei
Abstract: We report the first observations that connect a burst of fast flows and Pi2 fluctuations in the midtail current sheet at X ~ −60  R E with ground magnetic negative bays and Pi2 pulsations at high latitudes near 70°. Both the flow burst and negative bays occurred around midnight and were isolated and lasted for ~10 min. The flow burst had the characteristics of a low‐density plasma bubble. It was moving earthward at ~340 km/s and was accompanied by field‐aligned currents. The timing and equatorward motion of magnetic bays can be accounted for by this earthward moving bubble. Enhanced Pi2 fluctuations were observed within both the bubble and the magnetic bays. Pressure anisotropy with higher parallel pressure was observed associated with the flow burst and was firehose unstable. We discuss firehose instability as one of the possible mechanisms for the Pi2 fluctuations. Key Points: A flow bust at X  = −60  R E drove ground magnetic bay and Pi2 waves at 70 degree latitude Pi2 waves were enhanced within the flow burst and magnetic bay Firehose instability may be a possible mechanism for the Pi2 fluctuations